Research advances in cGAS–stimulator of interferon genes pathway and central nervous system diseases: Focus on new therapeutic approaches - Ding, Jiao; Dai, Yijie; Zhu, Jiahui; Fan, Xuemei; Zhang, Hao; Tang, Bo (Frontiers in Molecular Neuroscience, 2022)
Cyclic GMP–AMP synthase (cGAS), a crucial innate immune sensor, recognizes cytosolic DNA and induces stimulator of interferon genes (STING) to produce type I interferon and other proinflammatory cytokines, thereby mediating innate immune signaling. The cGAS–STING pathway is involved in the regulation of infectious diseases, anti-tumor immunity, and autoimmune diseases; in addition, it plays a key role in the development of central nervous system (CNS) diseases. Therapeutics targeting the modulation of cGAS–STING have promising clinical applications. Here, we summarize the cGAS–STING signaling mechanism and the recent research on its role in CNS diseases.